2022
DOI: 10.1039/d2ra02915d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and research of epoxy modified by carboxyl-terminated polybutylene adipate at room temperature

Abstract: In this study, carboxyl-terminated poly(butylene adipate) (CTPBA) was synthesized, which was terminated with epoxy and used as a toughening agent to modify the epoxy resin, and the modified epoxy resin was cured at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The resin matrix prepared by mixing 20 phr E-CTPBA and 100 phr E-51 was named CTPBA/EP. The detailed preparation method is set out in the literature [ 29 ].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resin matrix prepared by mixing 20 phr E-CTPBA and 100 phr E-51 was named CTPBA/EP. The detailed preparation method is set out in the literature [ 29 ].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In this paper, bisphenol A epoxy resin (E-51) was used as the research object, phenolic amine (T-31) was used as the curing agent, epoxy-terminated polybutylene adipate (E-CTPBA) was used as the toughening agent (self-made in the laboratory, adding 20 phr, where phr represents the amount of E-51 needed to add per 100 phr; in this paper phr is used as the standard; for the E-CTPBA preparation method see the literature [ 29 ]) and zinc powder was used as a filler. The effects of different amounts of zinc powder on the mechanical properties, bonding properties, thermodynamic properties and medium resistance of carboxyl-terminated polyester/epoxy resin (CTPBA/EP) composites were systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…In early studies [ 109 , 110 ], carboxyl end-seal tougheners and amino end-seal tougheners were widely used to improve the mechanical properties and fracture toughness of epoxy composites in order to enhance the delamination resistance of the composites. However, Marouf [ 111 ] showed that these conventional tougheners reduce the Tg , viscosity, and flexural strength of composites, and are not suitable for electronic packaging material applications.…”
Section: The Most Recent Solutions For Delamination Failurementioning
confidence: 99%
“…2021 [ 8 ], Lou, X. 2022 [ 23 ], Liu, H. 2022 [ 24 ], Sudprasert, P. 2023 [ 25 ], Yuan, Z. 2022 [ 26 ].…”
Section: Figurementioning
confidence: 99%